2004
DOI: 10.1682/jrrd.2004.03.0491
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between patellar-tendon-bearing and pressure cast prosthetic sockets

Abstract: This study compared the pressure distribution at the residual limb and socket interface in amputees wearing a pressure cast (PCast) socket system with amputees wearing the patellar-tendon-bearing (PTB) socket. The PCast system requires the subject to place his or her residual limb in a pressure chamber. Pressure is applied to the residual limb while the subject adopts a normal standing position. Four unilateral male amputees were fitted with both PTB and PCast sockets. Using a specially built strain-gauge-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 5 publications
0
25
1
Order By: Relevance
“…At late stance, the interface pressure at the proximal region of the anterior aspect increases, creating a more even distribution of interface pressure. This increase in proximal anterior pressure has also been shown by Goh et al [24,26]. However, the profiles observed for the sockets instrumented by Goh et al indicated a large difference in the distribution of pressure over the anterior aspect at late stance [24][25], which was not replicated in our study.…”
Section: Profile Over Anterior and Posterior Aspects Of Socketcontrasting
confidence: 61%
“…At late stance, the interface pressure at the proximal region of the anterior aspect increases, creating a more even distribution of interface pressure. This increase in proximal anterior pressure has also been shown by Goh et al [24,26]. However, the profiles observed for the sockets instrumented by Goh et al indicated a large difference in the distribution of pressure over the anterior aspect at late stance [24][25], which was not replicated in our study.…”
Section: Profile Over Anterior and Posterior Aspects Of Socketcontrasting
confidence: 61%
“…Earlier studies [4][5] have investigated a waterbased pressure cast (PCAST) socket. Another study compared the performance of a PCAST socket with a conventional hand-cast patellar tendon bearing (PTB) socket by recording residual limb-socket interface pressures in four adults with unilateral TT amputation [7]. Although the sample size of the study was small, it found the PCAST socket fit to be as successful as the PTB socket fit.…”
Section: Introductionmentioning
confidence: 99%
“…Lower limb prosthesis can be composed of several components such as the socket, liner, shank, ankle, and foot. Among these components socket and liner are the important parts of the prosthesis due to its interface among the residuum and socket [13]. Poor socket fitting due to enhanced pressure between socket and residuum greatly reduces the activity level of prosthetic users [4, 5].…”
Section: Introductionmentioning
confidence: 99%